Financial market regulation in the shadow of the sovereign debt crisis - Renate Mayntz (Max Planck Institute for the Study of Societies, 2013)
The financial market crisis of 2008/2009 triggered efforts at re-regulation at all political levels, national, European, and international. Reform demands had been radical and comprehensive but effective regulatory change was halting, and then in summer 2011 the related connected sovereign debt and euro crises came to preoccupy political attention. Regulatory financial market reform nevertheless continued. This paper traces both the shift in political attention and the continuing regulatory activities of different bodies between the summer of 2011 and the summer of 2013. The analysis highlights the time profile, the specific selectivity, the recursive nature, and the stepwise concretization of reforms. Finally, the issue is raised whether the reform process will eventually lead to increasing regulatory harmonization, or increasing international diversity of financial market regulation. – – Die Finanzmarktkrise von 2008/2009 hat auf allen politischen Ebenen - der nationalen, europäischen und internationalen - Versuche einer Regulierungsreform ausgelöst. Die anfänglichen Reformziele waren radikal und umfassend, aber der tatsächliche Reformprozess kam bis zum Sommer 2011 nur zögernd voran. Zu diesem Zeitpunkt drängte die Staatsschuldenkrise und die mit ihr verbundene Euro-Krise das Thema Finanzmarktregulierung in den Hintergrund. Das Discussion Paper verfolgt sowohl den Wandel politischer Aufmerksamkeit wie die dennoch weiter laufenden Aktivitäten wichtiger, speziell internationaler Institutionen in Sachen Regulierungsreform in der Zeit zwischen Mitte 2011 und Mitte 2013. Es wird gezeigt, dass der Reformprozess eine charakteristische Zeitstruktur, eine spezifische Selektivität und Rekursivität besitzt und durch eine schrittweise Konkretisierung gekennzeichnet ist. Am Ende stellt sich die Frage, ob der Reformprozess zu wachsender internationaler Harmonisierung oder umgekehrt zu wachsender Diversität von Finanzmarktregulierung führen wird.
Keywords: 300